2016
DOI: 10.1177/0887302x16675725
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Disposal System by Gifting

Abstract: The study of clothing disposal systems, involving the flow of clothing from one household to another, is of great interest because of the positive social and environmental consequences. Based on 35 in-depth interviews with adult men and women in Ecuador, a Latin American country, the authors sought to expand knowledge regarding one of these systems: clothing disposal by gifting to family, friends, and acquaintances. The respondents' narratives indicated that the clothing disposal system by gifting is noncentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
0
10
0
3
Order By: Relevance
“…Women were selected since, by virtue of being the largest consumers of clothing, they are also the largest disposers of clothing. Consumers of higher socioeconomic status are reported to be more involved in clothing disposal behaviors [11]. Prior researchers have also shown that older consumers are more likely to use the trash for apparel disposal than younger consumers (under the age of 35) [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women were selected since, by virtue of being the largest consumers of clothing, they are also the largest disposers of clothing. Consumers of higher socioeconomic status are reported to be more involved in clothing disposal behaviors [11]. Prior researchers have also shown that older consumers are more likely to use the trash for apparel disposal than younger consumers (under the age of 35) [5].…”
Section: Methodsmentioning
confidence: 99%
“…In a study of Ecuadorian households, older women were found to be instrumental in the mobilization of unwanted clothing that would be disposed of through gifting. Gift giving was found to be related to the interaction of the respondent with the clothing market system as well as an autonomous act where gifting was not due to a new purchase, for example, but rather, the act of giving [11].…”
Section: Consumer Apparel Disposalmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews adopted a semi-structured approach to allow for fluid conversation with participants and centred on the core themes of willingness to engage and barriers to engagement within each of the four models of collaborative consumption (buying second-hand, renting, sharing and swapping). The CFC modes of gifting/receiving gifted clothing and family re-use (handing down of items) (Cruz-Cárdenas,González, & Gascó, 2016;Klepp & Laitala, 2018) were not included in this examination of CFC, as a distinction was drawn between active (acquirer) and passive (recipient) consumption modes, with the focus here on the seeking out of collaborative consumption opportunities. This allowed a focus on the benefits of the modes considered within a commercial or business model framework.…”
mentioning
confidence: 99%
“…Percebe-se uma ênfase no que diz respeito ao comportamento de presentear ou (re)presentear que tratam de produtos de vestuário (CRUZ-CÁRDENAS; DEL VAL NÚÑEZ, 2016; CRUZ-CÁRDENAS et al, 2017). A literatura entende que o descarte como forma de presentear é mais demorado do que a doação, por exemplo, pois o processo de presentear necessita de uma identificação de potenciais destinatários do objeto (CRUZ-CÁRDENAS; DEL VAL NÚÑEZ, 2016).…”
Section: Devolverunclassified